THE CONCEPT OF INTIQALUL TA’ALLUM IN ISLAMIC RELIGIOUS EDUCATION: AN ANALYSIS OF MUHAMMAD ANWAR AL-SYARQOWI’S THOUGHT - Nuruddin, Mohammad; Muhlis, Achmad (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
Intiqalul Ta’allum, or transfer of learning, is a foundational concept in Islamic education that elucidates how knowledge, skills, and values acquired through learning can influence behavior and performance across different contexts. Although this concept is essential for strengthening the holistic competencies expected in Islamic Religious Education (PAI), including cognitive understanding, spiritual sensitivity, and moral conduct, scholarly discussions specifically examining Intiqalul Ta’allum from the perspective of Islamic thinkers remain limited. This article analyzes the conceptual framework of Intiqalul Ta’allum formulated by Muhammad Anwar al-Syarqowi and investigates its theoretical and pedagogical implications for PAI learning. Using a qualitative library research method, the study explores al-Syarqowi’s seminal work Al-Ta’allum: al-Nadhariyyat wa al-Tathbiqiyyah, supported by contemporary studies on transfer of learning and Islamic pedagogy. The findings reveal that al-Syarqowi views Intiqalul Ta’allum as an integrated process in which prior learning influences subsequent learning through general principles, specific-task similarities, and mediational cognitive processes. His framework expands the notion of transfer beyond cognitive knowledge, highlighting the movement of affective dispositions, spiritual values, and behavioral habits into real-life contexts. Within PAI, this concept underscores the importance of embedding religious teachings through meaningful learning experiences, sustained practice, and exemplary teacher conduct. Intiqalul Ta’allum thus provides a transformative pedagogical foundation that connects religious instruction with character formation, enabling students to demonstrate Islamic values consistently in school, family, and community settings. This perspective affirms the critical role of PAI in shaping learners who are intellectually capable, ethically responsible, and adaptive to contemporary social and moral challenges.